Effects of 12-week Circuit Exercise Intervention on Blood Pressure, Vascular Function, and Inflammatory Cytokines in Obese Older Women with Sarcopenia - Won-Sang Jung; Hana Ahn; Sung-Woo Kim; Hun-Young Park (Reviews in Cardiovascular Medicine, 2024)
Background: This study investigates the effects of a 12-week circuit exercise program on blood pressure, vascular function, and inflammatory cytokines in older obese women with sarcopenia. Methods: Twenty-eight older obese women with sarcopenia (mean age: 78.2 ± 3.7 years) were randomly divided into an exercise group (EG, n = 14) and a control group (CG, n = 14). The EG participated in a 12-week circuit exercise training regimen, conducted three times weekly, with each session lasting between 45 to 75 minutes (progressively increased over time). The CG was advised to maintain their regular daily routines throughout the intervention period. All dependent variables, including blood pressure, vascular function, and inflammation cytokines, were evaluated pre- and post-intervention. Results: Positive changes were observed in the EG in body composition (body fat mass; p < 0.001, body fat percentage; p < 0.01, free-fat mass; p < 0.01), blood pressure (heart rate; p < 0.05, rate pressure product; p < 0.01), vascular function (brachial–ankle pulse wave velocity; p < 0.05, flow-mediated dilation; p < 0.001), and inflammation cytokines (interleukin-6; p < 0.05). In the CG, there was an increase in body fat mass (p < 0.05) and body fat percentage (p < 0.05), while no changes were observed in other variables. Conclusions: The 12-week circuit exercise program significantly reduced blood pressure, improved vascular function, and decreased inflammatory cytokines in obese older women with sarcopenia. However, individual variations in response highlight the need for personalized exercise regimens.